2016
DOI: 10.1097/pas.0000000000000561
|View full text |Cite
|
Sign up to set email alerts
|

High-grade Transformation of Low-grade B-cell Lymphoma

Abstract: Patients with low-grade (clinically indolent) lymphomas are at risk to undergo transformation to high-grade (clinically aggressive) lymphoma, although transformation only occurs in a subset of patients. When transformation occurs it is a critical event that determines the course of disease and is associated with unfavorable patient outcomes. Accurate detection of transformation, predictive biomarkers, and identification of specific molecular pathways implicated in the pathobiology of transformation will facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 103 publications
1
16
0
Order By: Relevance
“…They postulated that the H/DC tumor arises from either a differentiated FL cell or a CPC at least at the pre-B-cell stage of differentiation. In contrast, Buser et al [74], who analyzed a compound pro-T LBL and indeterminate dendritic cell tumor simultaneously occurring at 3 different anatomical sites in a 59-year-old woman, found a tri (21) in both tumor components, whereas only the pro-T LBL additionally contained a monosomy (18) and NRAS G13D mutation. Therefore, they concluded that this composite tumor must have arisen by divergent cell differentiation from a CPC [74].…”
Section: Transdifferentiationmentioning
confidence: 99%
See 3 more Smart Citations
“…They postulated that the H/DC tumor arises from either a differentiated FL cell or a CPC at least at the pre-B-cell stage of differentiation. In contrast, Buser et al [74], who analyzed a compound pro-T LBL and indeterminate dendritic cell tumor simultaneously occurring at 3 different anatomical sites in a 59-year-old woman, found a tri (21) in both tumor components, whereas only the pro-T LBL additionally contained a monosomy (18) and NRAS G13D mutation. Therefore, they concluded that this composite tumor must have arisen by divergent cell differentiation from a CPC [74].…”
Section: Transdifferentiationmentioning
confidence: 99%
“…The 10-year risk of transformation in follicular lymphoma (FL), the most frequent low-grade B-NHL, ranges between 15 and 20%, with an annual transformation rate of about 2-3% [28]. Marginal zone lymphoma transforms into high-grade lymphoma in 10-14% of patients over time, although the true incidence rates of transformation are poorly documented [21].…”
Section: Intratumoral Heterogeneity In Lymphomamentioning
confidence: 99%
See 2 more Smart Citations
“…RS is also loosely applied to CLL/SLL patients who develop less common lymphoid neoplasms such as Hodgkin lymphoma (HL), plasmablastic lymphoma or Blymphoblastic leukemia/lymphoma. Whereas, histologic transformation occurs in patients with other types of low-grade B-cell neoplasms [3], the term RS is only used in the context of CLL/SLL.…”
Section: Introductionmentioning
confidence: 99%